2023
DOI: 10.3390/bs13020125
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Couriers’ Job Satisfaction through Social-Sustainability Practices: Perceived Fairness and Psychological-Safety Perspectives

Abstract: Due to the spike in online-retail demand during the pandemic, couriers confront increased workload and safety concerns, posing significant social-sustainability challenges for courier companies. This study explores the impact of social-sustainability practices on couriers’ job satisfaction in the context of the COVID-19 pandemic. We designed the research model from the theoretical lens of Maslow’s hierarchy of needs, equity, and psychological-safety theories. We collected the views of 428 couriers from the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…A research model was designed from the theoretical perspectives of Maslow's hierarchy of needs, fairness, and psychological safety theory. The results showed that social sustainability practices such as work environment, work conditions, health and safety, education and training had a positive impact on the work performance and job satisfaction of couriers during the epidemic through the mediation of psychological capital (Su ,2023). Zhou, et al (2018) research showed that psychological capital is positively correlated with job satisfaction of teachers, which can predict the variation of work engagement factors (vigor, dedication, focus).…”
Section: Psychological Capital Plays An Intermediary Rolementioning
confidence: 98%
“…A research model was designed from the theoretical perspectives of Maslow's hierarchy of needs, fairness, and psychological safety theory. The results showed that social sustainability practices such as work environment, work conditions, health and safety, education and training had a positive impact on the work performance and job satisfaction of couriers during the epidemic through the mediation of psychological capital (Su ,2023). Zhou, et al (2018) research showed that psychological capital is positively correlated with job satisfaction of teachers, which can predict the variation of work engagement factors (vigor, dedication, focus).…”
Section: Psychological Capital Plays An Intermediary Rolementioning
confidence: 98%
“…A program that uses safety as a starting point to operationalize sustainability should ideally place stress equally on the advantages of safety for people and the business aspects of pursuing safety measures [40] through mediators and social-sustainability practices, such as the work settings, working conditions, health and safety education and training, and the benefit of the couriers' employment satisfaction during the COVID-19 pandemic (psychological safety and perceived fairness) [41]. Programs for OCS and health help lure in and keep talent, which enhances the effectiveness of these organizations' internal operations.…”
Section: Safety Sustainabilitymentioning
confidence: 99%
“…Therefore, college mental health educators need to create an equal relationship with students through sincere listening, so that students can shed their camouflage and express their true ideas in the process of conversation. At the same time, students should not laugh at the dark part of their psychology, sincerely answer their doubts, reduce their psychological burden, cultivate their positive psychological state, and form a good world outlook, outlook on life and values [11][12].…”
Section: Listen Patientlymentioning
confidence: 99%